Analysis of technical and tactical principles in women's soccer - Pascual-Verdu, N.; Carbonell-Martinez, J. A. (Journal of Physical Education and Sport, 2018)
The aim of this article is to analyze the technical and tactical aspects observed during 30 first division women's soccer matches in the Iberdrola league 2016-2017 season. An observational analysis of the technical and tactical principles was carried out using the Longomatch programme with a template of corresponding categories. During this study a total of 18523 actions were registered of which 16535 (89.26%) were technical actions and 1988 (10.74%) were tactical. The most frequently realised technical actions were passing and ball control. The least frequent were balls skills and feints. When the number of technical actions realised in the first and second half of the match are compared, significant differences in the players taking possession (p=0.032) are found. In the case of tactical actions, the most common were interception and attack followed by support and losing one's marker. The least frequent were defensive splitting and the one-two. A significant difference was found in the tactical action of losing one`s marker between periods of the game (p=0.044). This investigation can be used by coaches to learn what technical and tactical aspects are the most used in matches and therefore plan their training sessions according to the demands of competition.